Fiscal aspects of the European monetary integration - Golubović Srđan (Zbornik Radova Pravnog Fakulteta u Nišu, 2014)
Along with the introduction of the euro as a single currency, importance of respecting the fiscal aspects which determine longevity of the monetary arrangement is recognized. For this reason, although underdeveloped, the EU fiscal system provides mechanisms to ensure fiscal discipline among member states. In addition to the fulfillment of the convergence criteria which is a precondition for joining the monetary union, they include no bailout clause and monetary financing prohibition. Sovereign debt that escalated in 2010 showed all the imperfections of these arrangements and pointed to the need for introduction of new and more effective fiscal rules. With fiscal system of the European Union as a starting point, the paper analyzes instruments defined by the fiscal system of the Union, which purpose is to ensure fiscal discipline of the European Monetary Union member states. Last part of the paper analyze new fiscal rules introduced as a response to the debt crisis in the Eurozone.